ERUCA SATIVA LINN.: PHARMACOGNOSTICAL AND PHARMACOLOGICAL PROPERTIES AND PHARMACEUTICAL PREPARATIONS - S JAAFAR, NOOR; S JAAFAR, IMAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Eruca sativa (jarjeer) is an annual herb (family Brassicaceae), which contains a wide range of chemicals and minerals with nutraceutical and organoleptic characteristics. Jarjeer was generally used as a food and traditionally mainly consumed due to its aphrodisiac properties. This crop known to contain various phytochemicals such as flavonoids, phenolic acids, terpens, carotenoids, tannins, glycosides, saponins, sterols, alkaloids, and other secondary metabolites. In leaves, kaempferol and its derivatives, glucosativin, are the main flavonoids and glucosinolate, respectively, while erucic acid and glucoerucin are the main fatty acid and glucosinolate, respectively. Medicinally, the plant has antibacterial, antidiabetic, antihypertensive, antiplatelet, and antioxidant activity and stimulates hair growth and other effects. Trails on topical pharmaceutical preparations involve the use of E. sativa which had been done. These preparations include creams and waxs which are intended to be used for potentiating hair growth and skin fungal and bacterial infection.